Sexual dimorphism and morphometric relationships in pelvic bones of Commerson's dolphins (Cephalorhynchus c. commersonii) from Tierra del Fuego, Argentina - Cáceres Saez, Iris (2014)
The hydrodynamic shape of the cetacean body and the reduction of the pelvic girdle leading to the loss of the pelvic limbs are the result of evolutionary adaptations to aquatic life; these changes are clearly represented in fossil remains (Thewissen et al. 2009)